Thematic analysis of middle school social studies textbooks regarding migration phenomenon - KOCALAR, ALİ OSMAN (My University, 2023)
Migration refers to the movement of individuals from the geography where they were born and raised to a different geography. People often migrate due to unfavourable conditions or factors such as poverty, illness, politics, food scarcity, natural disasters, war, unemployment, and lack of security. Migration movements lead to significant changes in the social, political, and economic structures of countries. In this regard, migration is a critically important societal phenomenon. The inclusion of such an influential societal phenomenon in education and teaching it to new generations in all its aspects is essential. One of the primary resources where the phenomenon of migration can be included in education is textbooks. An essential educational tool expected to address the migration phenomenon due to its interdisciplinary nature is social studies textbooks. This research aims to examine middle school social studies textbooks in the context of the migration phenomenon. To this end, the research was conducted using the document analysis method. Three textbooks determined by the random sampling method were the documents to be analysed. The study identified the reasons for migration, its outcomes, factors facilitating migration, activities that prevent and regulate migration, institutions regarding migration, concepts, definitions, classifications related to the teaching of migration, items and headings, visuals, and statistics in the examined textbooks. Consequently, informed recommendations were made to textbook writers.

Göç, insanların doğduğu ve büyüdüğü coğrafyadan farklı coğrafyaya doğru taşınma hareketidir. İnsanlar genellikle elverişsiz koşullardan veya yoksulluk, hastalık, politika, gıda kıtlığı, doğal afetler, savaş, işsizlik ve güvenlik eksikliği gibi faktörler nedeniyle göç etmektedir. Göç hareketleri ülkelerin sosyal, siyasal ve ekonomik yapısında önemli değişimlere neden olmaktadır. Bu yönüyle göç önemli bir toplumsal olgudur. Böylesine etkili bir toplumsal olgunun eğitime katılması ve yeni nesillere tüm yönleriyle öğretilmesi elzemdir. Eğitimde göç olgusunun yer alabileceği temel kaynaklardan birisi ders kitaplarıdır. Disiplinlerarası yapısı nedeniyle göç olgusuna yer vermesi beklenen önemli bir eğitim aracı ise sosyal bilgiler ders kitaplarıdır. Bu araştırmanın amacı ortaokul sosyal bilgiler ders kitaplarını göç olgusu bağlamında incelemektir. Bu amaçla araştırma doküman incelemesi yöntemiyle yürütülmüştür. Araştırmada rastgele örnekleme metoduyla belirlenen üç ders kitabı doküman olarak kabul edilmiştir. Araştırma sonucunda göç olgusunun nedenleri, sonuçları, göçü kolaylaştırıcı unsurlar, göçü önleyici ve düzenleyici faaliyetler, göçle ilgili kurumlar, göçün öğretimiyle ilgili kavramlar, tanımlar ve sınıflamalar, madde ve başlıklar, görseller ve istatistikler tespit edilmiştir. Ders kitabı yazarlarına öneriler getirilmiştir.
Küresel iklim değişikliğinin toplumda meydana getirdiği farkındalıklar
Keywords: Migration; Education; Social Studies; Textbook Review; Document Analysis; Göç; Eğitim; Sosyal Bilgiler; Ders Kitabı İnceleme; Doküman Analizi